ANAK USIA 5-6 TAHUN MELALUI PERMAINAN MENEMPEL HURUF DI PAPAN FLANNEL DI KELOMPOK B1 TK BHAYANGKARI BAGANSIAPIAPI KABUPATEN ROKAN HILIR - Rozana, Rozana; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is an underdeveloped ability to recognize letters in children aged 5-6 years optimally among children has not been able to: mention the letter symbols familiar, familiar voice initial letter of the name of the existing objects mentioned by teacher , understand the relationship between sound and form of letters and have not been able to read his own name and mention the initial letter of the name by using a flannel board.Therefore, researchers make improvements and optimize the child's ability to recognize letters according to the level of development of age. The purpose of the implementation of this study was to determine the ability of children recognize letters through the flannel board games, and to know the high increase in the ability of children through the game recognize letters attached letter in flannel board in children aged 5-6 years in kindergarten B1 group Bhayangkari Bagansiapiapi Rokan Hilir. This research is a classroom action research conducted in two cycles. In one cycle there are three meetings. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 15 children consisting of 9 boys and 6 girls. Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action to the first cycle of 33.90%, the first cycle to the second cycle of 36.90%, and increased from the prior cycle to cycle II of 83.40%. From the results of these studies concluded that through the game to stick the letters on the flannel board can improve the ability to know the letters in children aged 5-6 years in kindergarten Bhayangkari Bagansiapiapi Rokan Hilir.Keyword: Sticking Games, Flannel Boards